Contemporary economics - McEachern, William A. (Thomson South-Western, 2008)
Bring economics to life with rich, practical examples that make concepts clear and intriguing. CONTEMPORARY ECONOMICS blends economic expertise and educational insights with comprehensive content, sound instructional design, and extensive print and media teaching tools. This new edition now includes two chapters covering personal finance, including information on managing money and being a responsible consumer.